Of Gardens, Forests, and Parks - Peter J. Katzenstein (Uncertainty and Its Discontents: Worldviews in World Politics, 2022)
Expressing the predictable and controlled and the unpredictable and uncontrollable as unavoidably linked aspects of human experience in the real world, gardens and forests (or jungles) serve here as metaphors grounded in different fields of human endeavor. Section 10.1 of this chapter explores some of these. Section 10.2 explores the garden of experiments and the forest of experimentation as different ways of operating under conditions of putatively controllable risk and acknowledged uncertainty. Section 10.3 concludes by considering parks as a hybrid of garden and forest, a terrain where Newtonianism and Post-Newtonianism can overlap. It also discusses the role of values in worldviews and discusses science and religion as the two reigning worldviews that help us understand and navigate an uncertain world.
Keywords: 320